2020
DOI: 10.30919/esmm5f920
|View full text |Cite
|
Sign up to set email alerts
|

Study on Design, Synthesis and Controlled Color Emission of (Gd,Y)AG: Ce3+ Based Phosphors Through Replacing Al3+ Partly

Abstract: Owing to its excellent yellow light emission, the (Gd,Y)AG:Ce 3+ based phosphors have been widely studied. In this paper, the (Gd,Y)3(Al1-xGax)5O12:Ce 3+ (x=0.1-0.8) and (Gd,Y)3(Al1-2yMgySiy)5O12:Ce 3+ (y=0.05-0.4) phosphors were successfully prepared by coprecipitation and high temperature solid phase method, respectively. The lattice stabilization, microstructure and fluorescence properties were systematically investigated. With increasing the concentration of Ga 3+ , the emission peaks of (Gd,Y)3Al5O12:Ga 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The (Gd,Y)AG:Ce 3+ based phosphors have attracted much attention because of the excellent yellow light emission properties. Ma et al [5] partly substituted Al 3+ in (Gd,Y)AG:Ce 3+ by Ga or Mg, Si ions, and observed tunable color emission as the concentrations of the compositions changed. As for ceramic composites, Yang et al [6] added 0.3% content of graphene platelets to the Si3N4/SiC ceramics.…”
mentioning
confidence: 99%
“…The (Gd,Y)AG:Ce 3+ based phosphors have attracted much attention because of the excellent yellow light emission properties. Ma et al [5] partly substituted Al 3+ in (Gd,Y)AG:Ce 3+ by Ga or Mg, Si ions, and observed tunable color emission as the concentrations of the compositions changed. As for ceramic composites, Yang et al [6] added 0.3% content of graphene platelets to the Si3N4/SiC ceramics.…”
mentioning
confidence: 99%